Development of Geospatial Database for Public Schools Data Management in Osogbo, Osun State - Awoniyi, Anthony Ilufoye (2015)
This study aimed at building a geospatial database containing information on infrastructural facilities, staff profiles and enrolment characteristics in public schools in Osogbo, Osun State. This was with a view to enhancing the monitoring and management of school systems using Geographical Information System (GIS) tools. The specific objectives were to carry out an inventory of infrastructural facilities, biodata of teachers and children enrolments in public schools in Osogbo, produce a map of Osogbo showing the locations of public schools and create a geospatial database containing basic information such as infrastructural facilities, teachers' biodata and children enrolments in public schools in the area.